ANXIETY, STRESS, AND ANGER: THE IMPACT OF COVID-19 ON UNIVERSITY STUDENTS’ MENTAL HEALTH - Reyes, Nicolás (2021)
Since March 14, 2020, Ecuador has experienced a state of alarm due to the global and local health crisis that has included extensive social isolation of the population, the stoppage of productive work and the closure of educational centers of all levels that have affected daily life, reconfigured the concept of normality and seriously affected family economies. This article describes how the confinement affected university students, who have lived through stages of stress, depression, and anger, since their routine, their social world and daily life changed dramatically. The sensations and feelings that the confinement of more than 100 days has produced in university students are described using the ethnographic tale. The forced confinement or quarantine has caused a series of problems in social, family and affective behavior, increasing states of anxiety, anguish, stress and anger that are mixed with uncertainty because of the serious problems related to the loss of jobs, increase in poverty, social inequalities, social panic and impacts on mental health caused by the fear of infection or loss of loved ones, as it is experienced in the country, generating an unprecedented crisis